Glucocorticoid Functional Reserve in Full-Spectrum Intensity of Primary Hypothyroidism - Rodríguez Gutiérrez, René; González Velázquez, Camilo Daniel; González Saldívar, Gerardo; Villarreal Pérez, Jesús Zacarías; González González, José Gerardo (2014)
Adrenal function might be impaired in patients with primary hypothyroidism.The objective was to evaluate adrenocortical function using the low-dose cosyntropin test in patients with primary hypothyroidism. Consequently a prospective, longitudinal, controlled study of sixty adult patients with primary hypothyroidism was carried out. Patients na¨ıve to L-T4 treatment were compared with control participants. A low-dose cosyntropin test was done before and after L-T4 therapy. Thirty and sixty minutes after the lowdose cosyntropin, the mean cortisol values were lower in the cases group (612.6 ± 133.1 and 603.4 ± 153.7 nmol/L) when compared to the control group (677.0 ± 82.4 and 669.9 ± 83.7 nmol/L) (